2006
DOI: 10.1507/endocrj.k05-167
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ghrelin, IGF-I and IGFBP-3 Levels In Children with Normal Variant Short Stature

Abstract: Abstract. This study is planned to investigate the role of ghrelin in normal variant short stature. Serum ghrelin, IGF-I and IGFBP-3 levels were measured in 17 children with constitutional delay of growth, 19 children with familial short stature and 11 age matched healthy children. Mean bone age of the constitutional delay of growth group was lower compared to other groups. Constitutional delay of growth group had lower mean weight compared to the controls. Serum IGF-I values were lower in the constitutional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
5
18
0
Order By: Relevance
“…In spite of using this assay we observed that ISS patients had a higher mean serum ghrelin level than controls and, moreover, 10 patients with ISS had ghrelin levels greater than 2 SD. This finding is in agreement with Camurdan et al [25], who recently investigated the role of ghrelin in normal variant short-statured patients. Ghrelin levels were higher in the short stature groups compared to controls.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In spite of using this assay we observed that ISS patients had a higher mean serum ghrelin level than controls and, moreover, 10 patients with ISS had ghrelin levels greater than 2 SD. This finding is in agreement with Camurdan et al [25], who recently investigated the role of ghrelin in normal variant short-statured patients. Ghrelin levels were higher in the short stature groups compared to controls.…”
Section: Discussionsupporting
confidence: 93%
“…Instead, higher ghrelin levels may reflect the orexigenic action of this peptide to increase weight in children with ISS. Camurdan et al [25] reported an inverse relationship between absolute values of IGF-I and ghrelin levels in short-statured patients with a mean age of 11 years. In contrast, we observed a positive correlation between ghrelin and IGF-I SDS only in females.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding is interesting, because in conditions affecting appetite and growth adversely, ghrelin has been shown to increase [12,23]. Although our patient group was in acceptable limits regarding overall appetite and growth, and this was our intention in order to exclude the effects of body size on leptin levels, IDA is crudely a catabolic state.…”
Section: Discussionmentioning
confidence: 91%
“…height, weight and BMI). In a study among children with normal variant short stature ghrelin was increased and negatively correlated with height SDS in short children [23].…”
Section: Discussionmentioning
confidence: 94%
“…Underweight children have been found to have elevated ghrelin levels, but only one study has shown low height SD score (SDS) as an independent determinant of elevated AG levels in children with idiopathic short stature (10,11). Recently, in several patients, however, a missense mutation resulting in a complete loss of GHSR constitutive activity has been implicated in short stature with dominant transmission (12).…”
mentioning
confidence: 99%